Integrasi Budaya Lokal Dalam Iklan Sebagai Strategi Pemasaran Produk Global - Shambodo, Yoedo; Ibrahim, Fachmi; Ismah, Syadiyah Nur; Katigo, Zahrio Herlanda (CommLine, 2025)
Cultural integration is an important approach in an increasingly connected global environment, enabling organizations to respect and utilize cultural diversity to achieve their goals more effectively. This research highlights the importance of understanding and utilizing local cultural elements in global brand marketing campaigns to increase product appeal in local markets through advertising activities designed by advertising agencies. Advertising agencies have a key role in this process, as they are responsible for creating advertising content that is culturally sensitive and relevant to target audiences in different parts of the world. One of the global companies or brands that is trying to integrate culture in its advertising is Lalamove through the global campaign "Make a Winning Move" through the advertising agency they appointed, namely Froyonion HQ. This research uses qualitative methodology with interview and documentation methods. The key informant in this research is the Froyonion HQ creative team who designed advertisements from Lalamove and documentation from various sources. The results of the study concluded that cultural integration in advertising includes the use of several cultural elements such as language systems, livelihood systems and social systems. The Lalamove ad shows the importance of understanding local culture in the context of global brand marketing. With an approach that respects local culture, Lalamove not only creates attractive advertising but also wants to build consumer loyalty.